Urban mosques among high-rise : the issue of parking efficiency within compact urban settings - Nangkula Utaberta,; Nur Fatin Mohd Sauffie,; Chang, Sook Yee; Nayeem Asif, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Car park facilities was one of the concerns in mosque design especially when the mosque is situated among dense high-rise buildings. High number of worshippers during Friday prayers has been leading to a huge demand of parking areas around the mosque. Insufficient of parking areas might result in illegal parking happen around the mosque and produces trouble to the local citizens. This study will study on the efficiency of the parking areas in and around the mosque in urban area.